2005
DOI: 10.1055/s-2005-837618
|View full text |Cite
|
Sign up to set email alerts
|

Plantar Flexion Torque as a Function of Time of Day

Abstract: The possible peripheral and/or central origin in the mechanisms responsible for day-time fluctuation in maximal torque of the triceps surae muscle were investigated with a special emphasis on antagonist muscle coactivation. Eleven healthy male subjects (physical education students) took part in this investigation. The electromechanical properties of the plantar flexor muscles were recorded at two different times of day: between 06:00 h and 08:00 h in the morning and between 17:00 h and 19:00 h in the evening. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
2
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 17 publications
4
24
2
1
Order By: Relevance
“…In agreement with the previous study (Guette et al 2005b), we observed a lower MVC torque and concomitant soleus muscle EMG ratio that was associated with a constant peak-twitch torque at M max . The present findings point to a nochange in the efficiency of the reflex transmission between Ia spindle afferent input and soleus a-motoneuron pool according to the time of the day.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with the previous study (Guette et al 2005b), we observed a lower MVC torque and concomitant soleus muscle EMG ratio that was associated with a constant peak-twitch torque at M max . The present findings point to a nochange in the efficiency of the reflex transmission between Ia spindle afferent input and soleus a-motoneuron pool according to the time of the day.…”
Section: Discussionsupporting
confidence: 93%
“…Nevertheless, studies concerning plantar flexor muscles (Castaingts et al 2004;Guette et al 2005b) are less consistent. In fact, in voluntary submaximal conditions, Castaingts et al (2004) described a lower neuromuscular efficiency (i.e.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The difference between the peaks and nadirs in fitness indices is up to about 20%, except for flexibility, which shows a larger difference with its lowest value at midnight. Two notable reports 31,32) have investigated the circadian rhythms of muscle strength. In these reports, maximal voluntary plantar flexion torque was 5-7% higher in the morning than in the evening.…”
Section: A Variety Of Human Circadian Rhythms and Characteristicsmentioning
confidence: 99%
“…To elucidate the mechanisms, the test session of those studies included measurements during tetanic contractions using the electrical stimulation technique. The authors suggested that possible mechanisms underlying the decreased plantar flexion torque in the evening might be a decrement in soleus muscle central command 31) and higher fatigue state in the fastest-twitch motor units in the weight-bearing soleus muscle 32) . As these studies did not strictly control the subjects' behavior, results may differ by employing a "constant routine" protocol.…”
Section: A Variety Of Human Circadian Rhythms and Characteristicsmentioning
confidence: 99%